Regional Conference on the Phase-Out of Leaded Gasoline in Sub-Saharan Africa : Proceedings - Bultynck, Patrick (World Bank, Washington, DC, 2014)
Leaded gasoline is the greatest single source of human exposure to lead, and as such, the health impacts of lead are serious, affecting, and causing elevated blood pressure, cardiovascular conditions, neurological and kidney disease, among many others. While over eighty percent of the gasoline sold worldwide is now lead-free, Africa remains the exception. The specific objectives of the regional conference on the phase-out of leaded gasoline in Sub-Saharan Africa were to raise awareness about the health impacts of leaded gasoline, and build consensus among stakeholders on the technical, regulatory, institutional, economic issues, and the priorities for implementing lead phase-out programs, in addition to develop action plans to phase-out leaded gasoline, with a timetable, and monitoring indicators. The proceedings include the topics covered at the conference, i.e., air quality monitoring, environmental lead levels in African cities, and air quality guidelines, and monitoring programs. Regarding pricing and regulatory issues, topics addressed covered economic and financial incentives; regulation, standards, and enforceable balance, while policy strategies included the promotion of public transport, land use control, and city planning. Cases studies were explored regarding successful programs of lead phase-outs, covering oil importing and exporting countries with, or without refineries.